2019
DOI: 10.3389/fonc.2019.01363
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of the Endocannabinoid Modulating Enzymes Fatty Acid Amide Hydrolase and N-Acylphosphatidylethanolamine-Specific Phospholipase D in Endometrial Carcinoma

Abstract: Background: The concentrations of three N-acylethanolamines (NAEs), anandamide (AEA), N-oleoylethanolamide (OEA), and N-palmitylethanolamide (PEA) are increased in the endometria of women with endometrial cancer (EC). It is widely accepted that plasma levels of these three NAEs are regulated by the actions of the rate-limiting enzymes N-acylphoshatidylethanolamine-specific phospholipase D (NAPE-PLD) and fatty acid amide hydrolase (FAAH), which are synthesizing and degradative, respectively. The expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The latter investigation also reported elevated 2-AG levels as a result of strong overexpression of DAGL α with less pronounced MAGL induction in hepatocellular cancer tissue; downregulation of AEA was found to be thereby dependent on higher expression levels of FAAH. In contrast to these observations, a decrease in FAAH protein expression and an increase in NAPE-PLD in cancerous versus non-cancerous endometrial tissue has recently been reported [61], resulting in increased AEA and PEA levels in cancerous endometrial tissue and in plasma from patients with endometrial carcinoma compared to volunteers with an atrophic endometrium [60].…”
Section: Regulation Of Endocannabinoid-synthesising and -Degrading Enzymes In The Tumour Processmentioning
confidence: 82%
“…The latter investigation also reported elevated 2-AG levels as a result of strong overexpression of DAGL α with less pronounced MAGL induction in hepatocellular cancer tissue; downregulation of AEA was found to be thereby dependent on higher expression levels of FAAH. In contrast to these observations, a decrease in FAAH protein expression and an increase in NAPE-PLD in cancerous versus non-cancerous endometrial tissue has recently been reported [61], resulting in increased AEA and PEA levels in cancerous endometrial tissue and in plasma from patients with endometrial carcinoma compared to volunteers with an atrophic endometrium [60].…”
Section: Regulation Of Endocannabinoid-synthesising and -Degrading Enzymes In The Tumour Processmentioning
confidence: 82%
“…Interestingly, AEA levels were elevated in lymphatic metastasis [ 25 ] and in endometrial cancer (EC) tissue compared to non-cancerous tissues. Moreover, FAAH was reduced while NAPE-PLD was increased in EC [ 26 ]. In another study, NAPE-PLD and MAGL expression was upregulated in colorectal cancer tissue [ 25 , 27 , 28 ], furthermore, high MAGL expression was indicative of a poor prognosis for patients compared to those with a low expression of MAGL [ 29 ].…”
Section: Ecs In Cancermentioning
confidence: 99%
“…Firstly, we measured the relative levels of the transcripts for FAAH and NAPE-PLD in the two cell lines. FAAH and NAPE-PLD have been shown to be expressed in endometrial carcinoma (Ayakannu et al, 2019) and Ishikawa cells (Fonseca et al, 2018). However, it was necessary to confirm that HEC-1A cells also express FAAH and NAPE-PLD (Figure 3).…”
Section: Transcript Levels Of the Ecs Enzymes In Untreated Ishikawa Amentioning
confidence: 99%